A Related Party Transactions, Family Firms and Firm Performance - Mohammed, Nishtiman (Accounting Analysis Journal, 2019)
The objective of this study is to examine the relationship between related party transactions and firm performance in the presence of family ownership. The study used data of 714 public listed firms in Istanbul stock exchange for the period of 2011-2015.Utilizing regression analysis of 714 Turkish listed firms, this study shows that related party transaction has a negative influence on firm performance. In addition, the study shows that this association is stronger in the presence of family ownership. The results proposed that a related party transaction is practiced by family firms to expropriate minority shareholders rights. The result is consistent with entrenchment hypothesis and tunneling.